Financial services in the trading system : progress and prospects - Miller, Eric (INTAL-ITD Buenos AiresAR, 1999)
Examines both how and why trade in financial services entered on to negotiating agendas at the regional and global levels and assessest the evolution of international disciplines in this area to date. Focuses on Canada-United States Free Trade Agreement (CUSFTA), NAFTA and the WTO Agreement on Trade in Financial Services.